On the ?-differentiability of mappings of Banach spaces - Gretskii, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the monogeneity conditions for ℝ-differentiable mappings of domains of a Banach space and establish criteria of ℂ-differentiability of a mapping at a point.